Defect of platelet function associated with chronic hypoglycaemia. Issue 1 (January 1976) - Hutton, R A; Macnab, A J; Rivers, R P
Abstract : Two patients are described with chronic hypoglycaemia; the first having glucose-6-phosphatase deficiency (type I glycogen storage disease), and the second fructose 1:6-diphosphatase deficiency. Both cases were associated with a bleeding diathesis, a defect of platelet aggregation, and a deficiency of platelet adenine nucleotides. The effect on the platelet abnormalities of a period of normoglycaemia was studied in both patients. Correction of the platelet abnormalities occurred rapidly after stabilization of the blood glucose within the normal range. Normal function persisted for the duration of the normoglycaemia, facilitating diagnostic liver biopsy and surgical procedures. A biochemical explanation for the nucleotide deficiency is suggested.